Aggressive Behaviors and Suicide Ideation in Inpatient Adolescents: The Moderating Roles of Internalizing Symptoms and Stress - BUITRON, VICTOR (Suicide Life Threat Behav, 2017)
The present study examined a conceptual model in which the association between aggressive behaviors and suicide ideation is moderated by internalizing symptoms and ongoing stress. Participants were 304 psychiatric inpatient adolescents (65.8% girls) ranging in age from 12 to 17 years (Mean age = 14.69). The association between aggressive behaviors and suicide ideation was significantly moderated by internalizing symptoms and ongoing stress; the association was positive in adolescents low in internalizing symptoms or high in ongoing stress, but negative in adolescents high in internalizing symptoms or low in ongoing stress. The three-way interaction between aggressive behaviors, internalizing symptoms, and ongoing stress was not statistically significant. The current findings indicate that in adolescents who display high levels of aggressive behaviors, the presence of high ongoing stress provides a more useful indicator of levels of suicide ideation than the presence of high internalizing symptoms. implications for case identification and prevention are discussed.